Pelimpahan Wewenang Dokter Kepada Perawat Pada Tindakan Peresepan Obat Anti Tuberkulosis Paru Di Puskesmas - Situmorang, Friedrich Rabin (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
This research examines the delegation of authority from doctors to nurses in prescribing Anti-Tuberculosis Drugs (OAT) at Community Health Centers (Puskesmas). The study aims to analyze the legal basis for such delegation and determine the legal responsibilities of doctors when delegating prescribing authority to nurses. This normative juridical research employs statutory and conceptual approaches, utilizing primary, secondary and tertiary source of legal materials. The findings reveal that delegation of OAT prescribing authority is legally permissible through mandate or delegation mechanisms, provided it meets strict requirements: written documentation, nurse competency verification, and continuous supervision. However, the doctor retains ultimate legal responsibility for clinical decisions under the mandate mechanism, while nurses bear professional responsibility for the technical execution of delegated tasks. Negligence in delegation may result in disciplinary, civil, administrative, or criminal liability. The study recommends establishing national technical guidelines for delegation in TB services and strengthening standard operating procedures at Puskesmas to ensure legal certainty and patient safety.